Developing a Primary Care–Focused Intervention to Engage Patients With Osteoarthritis in Physical Activity: A Stakeholder Engagement Qualitative Study. Issue 1 (January 2022) - Griesemer, Ida; Vu, Maihan B.; Callahan, Leigh F.; Cleveland, Rebecca; Golightly, Yvonne M.; Grimm, Kimberlea; Huffman, Katie; Nelson, Amanda E.; Rees, Jennifer; Allen, Kelli
Physical activity (PA) is important for managing osteoarthritis (OA), but many patients are inactive. Research is needed on strategies to leverage clinical encounters to engage patients in PA. Guided by the socioecological model of health behavior, this study aimed to engage stakeholders in the process of refining an Osteoarthritis Physical Activity Care Pathway (OA-PCP). Six focus groups and seven individual interviews were conducted with key stakeholders. Focus groups were specific to stakeholder roles and included patients with OA, support partners, and clinic personnel ( n = 6 focus groups). Interview participants were local and national PA program representatives ( n = 7 interviews). Data were analyzed by thematic analysis. Themes identified in the data included ways the OA-PCP can help patients with OA address challenges to PA engagement, strategies for connecting patients with PA resources, methods for implementing OA-PCP into clinical settings and potential use of PA trackers in the OA-PCP program. Stakeholders' comments were summarized into key recommendations for OA-PCP. Some recommendations reinforced and led to refinements in planned aspects of OA-PCP, including tailoring to individual patients, involvement of a support partner, and addressing pain with PA. Other recommendations resulted in larger changes for OA-PCP, including the addition of three email- or mail-based contacts and not requiring use of a PA tracker. The refined OA-PCP program is being evaluated in an exploratory trial, with the ultimate goal of establishing a PA program for OA that can be successfully implemented in clinical settings.